Depression and severity of glaucoma among older adults in urban and suburban areas - Sangeetha Tharmathurai; Muhammad Ikmal Mohamad Kamil; Asrenee A. Razak; Jemaima Che Hamzah; Azhany Yaakub; Qamaruddin Fazilawati; Liza-Sharmini Ahmad T. (Wolters Kluwer Health, Inc., 2021)
Summary: Depression increases with severity of visual field defect in older adults with primary open-angle glaucoma (POAG).